TINJAUAN FIKIH MUAMALAH TERHADAP PEMANFAATAN PASIR DI JORONG SUNGAI EMAS NAGARI SARUASO KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - Riski Hidayat; Afrian Raus (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The point in this issue is that there are several contracts that occur in the use of sand and how the fiqh muamalah views regarding the contracts that are made in the use of sand. The purpose of this research is to find out and explain the contracts used in the use of sand in Jorong Sungai Emas Nagari Saruaso, Tanjung Emas District, Tanah Datar Regency, and to find out and explain the muamalah fiqh review of the use of sand in Jorong Sungai Emas Nagari Saruaso, Tanjung Emas District, Tanah Datar Regency. The type of research that the authors use is a type of field research (field research) which is descriptive qualitative. Primary data sources consist of managers, land owners, sand buyers and workers, while secondary sources are through books and other reading sources that have something to do with the title of the researcher who can provide additional information or data that strengthens the primary data. Data collection techniques used in this study were interviews and documentation. Data validity assurance techniques with source triangulation. The results of the study illustrate that in the implementation of the use of sand in Jorong Sungai Emas Nagari Saruaso, Tanjung Emas District, Tanah Datar Regency, namely; First, the forms of contracts that occur in sand utilization activities are syirkah mudharabah or profit sharing contracts, namely profit sharing contracts between investors and managers, then leasing contracts, namely contracts between managers and landowners in the form of island money and sale and purchase agreements, namely contracts made between the purchaser and the manager.Second, the use of sand in Jorong Sungai Emas Nagari Saruaso, Tanjung Emas District, Tanah Datar Regency, in terms of Fiqh Muamalah, it was found that the sale and purchase agreement between the manager and the buyer did not meet the legal requirements of the sale and purchase, namely that the object must be owned by himself, while the measure made by the craftsman loading or workers do not have a standard measure sometimes the sand is loaded in excess of the measure and sometimes less than the measure then the contract being made becomes invalid to do.